Malignant Cerebellar Edema Subsequent to Accidental Prescription Opioid Intoxication in Children - Duran, Daniel; Messina, Robert D.; Beslow, Lauren A.; Montejo, Julio D.; Karimy, Jason K.; Gavankar Furey, Charuta; Sheridan, Alison D.; Sze, Gordon; Yarman, Yanki; DiLuna, Michael L.; Kahle, Kristopher T. (Frontiers in Neurology, 2017)
We present two recent cases of toddlers that developed malignant cerebellar edema subsequent to accidental ingestion of prescription opioids. Both children presented acute neurological decline, hydrocephalus, and tonsillar herniation requiring emergent ventricular drain placement, suboccipital craniectomy, and partial cerebellectomy. Together with several other reports, these cases suggest the existence of an uncommon yet severe syndrome of acute opioid-induced malignant cerebellar edema. We hypothesize that the condition results from a combination of primary opioid receptor-mediated changes in neuronal metabolism that are exacerbated by secondary hypoxic insult. If recognized promptly, this syndrome can be treated with emergent neurosurgical intervention with good clinical outcomes. These cases also illustrate the unintended consequences and innocent victims of the spiraling prescription opioid epidemic, which will likely increase in prevalence. Recognition of this syndrome by clinicians is thus critical.